Growth and magneto‐optical characteristics of cerium‐doped terbium gallium garnet by the floating zone method. Issue 7 (28th May 2015) - Chen, Zhe; Yang, Lei; Hang, Yin; Wang, Xiangyong
<x xml:space="preserve">Abstract</x> This article describes cerium‐doped terbium gallium garnet single crystals having excellent magneto‐optical properties grown by a floating zone growth method. The flawless crystalline, high transparency and low absorption loss enable our novel crystal material to use in the visible‐near‐infrared Faraday devices.